2009 24th Annual IEEE Conference on Computational Complexity 2009
DOI: 10.1109/ccc.2009.41
|View full text |Cite
|
Sign up to set email alerts
|

Regularity, Boosting, and Efficiently Simulating Every High-Entropy Distribution

Abstract: We show that every high-entropy distribution is indistinguishable from an efficiently samplable distribution of the same entropy. Specifically, we prove that if D is a distribution over {0, 1}n of min-entropy at least n − k, then for every S and there is a circuit C of size at most S · poly( −1 , 2 k ) that samples a distribution of entropy at least n − k that is -indistinguishable from D by circuits of size S.Stated in a more abstract form (where we refer to indistinguishability by arbitrary families of disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
86
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(86 citation statements)
references
References 12 publications
0
86
0
Order By: Relevance
“…In [25], this result is used to prove that every high-entropy distribution is indistinguishable from an efficiently samplable distribution of the same entropy. Moreover, it is shown that many fundamental results including the Dense Model Theorem [23,14,21,10,24], Impagliazzo's hardcore lemma [18] and a version of Szémeredi's Regularity Lemma [11] follow from this theorem.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In [25], this result is used to prove that every high-entropy distribution is indistinguishable from an efficiently samplable distribution of the same entropy. Moreover, it is shown that many fundamental results including the Dense Model Theorem [23,14,21,10,24], Impagliazzo's hardcore lemma [18] and a version of Szémeredi's Regularity Lemma [11] follow from this theorem.…”
mentioning
confidence: 99%
“…2 A dependency on ε −1 is also necessary. Indeed, Trevisan et al [25,Rem. 1.6] show that such a dependency is necessary for the simulator h in (1).…”
mentioning
confidence: 99%
See 3 more Smart Citations